Increased expression of transforming growth factor α precursors in acute experimental colitis in rats. Issue 2 (1st August 1997) - Hoffmann, P; Zeeh, J M; Lakshmanan, J; Wu, V S; Procaccino, F; Reinshagen, M; McRoberts, J A; Eysselein, V E
Abstract : Background and aim —Epidermal growth factor (EGF) and transforming growth factor α (TGF-α), members of the EGF family of growth factors, protect rat gastric and colonic mucosa against injury. Having shown previously that exogenously applied EGF protects rat colonic mucosa against injury, the aim of the present study was to evaluate the endogenously expressed ligand mediating the protective effect of EGF/TGF-α in vivo. Methods —In an experimental model of trinitrobenzene sulphonic acid (TNBS)/ ethanol induced colitis in rats EGF and TGF-α expression was evaluated using a ribonuclease protection assay, northern blot analysis, western blot analysis, and immunohistochemistry. Results —TGF-α mRNA increased 3–4 times at 4–8 hours after induction of colitis and returned to control levels within 24 hours. TGF-α immunoreactive protein with a molecular size of about 28 kDa representing TGF-α precursors increased markedly after induction of colitis with a peak at 8–12 hours. No fully processed 5.6 kDa TGF-α protein was detected in normal or inflamed colon tissue. Only a weak signal for EGF mRNA expression was detected in the rat colon and no EGF protein was observed by immunohistochemistry or western blot analysis. Conclusions —TGF-α precursors are the main ligands for the EGF receptor in acute colitis. It is hypothesised that TGF-α precursors convey the biological activity of endogenous TGF-α peptides during mucosal defence and repair.